Biology and Management of Eggplant (Solanum melongena L.) Shoot and Fruit Borer: A Review - Siam, M A Habib; Arafeen, Mohammad Shamsil; Dey , D; Owaresat, J K (Journal of the Bangladesh Agricultural University, 2024)
Eggplant (Solanum melongena Linnaeus) is a vital crop in South Asia, valued for its use in both raw and cooked dishes. However, its cultivation is severely threatened by the eggplant shoot and fruit borer, Leucinodes orbonalis (Guen.), which damages the plant from the seedling stage to harvest. The larval phase of this pest bores into shoots and fruits, potentially causing up to 90% loss and a decline in quality. Farmers often use excessive insecticides to combat L. orbonalis, leading to residue accumulation in food, insecticide resistance, pest resurgence, secondary pest outbreaks, and harm to beneficial organisms and the environment. In South Asia, this pest is the primary threat to eggplant fields, attracting significant research attention. This review paper examines biology, damage and control measures of eggplant shoot and fruit borer including resistant and tolerant varieties, sex pheromone traps, physical and mechanical barriers, biopesticides, biocontrol agents, and cultural and chemical methods, supported by previous studies and research findings. J Bangladesh Agril Univ 22(3): 267-276, 2024